The Improvement Perspectives of the Institute of Legislative Initiative in Republic of Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The most basic social relations in society are regulated by laws. The process of creating a law begins with the implementation of a legislative initiative.